(untitled) (Fiep Bulletin - online, 2019)
The Physical Education in Basic Education is a curricular component, which has specifics and contents to be exploredand, why not, be used as a tool for research, as a mechanism to facilitate Scientific Initiation? Physical Education has aneducational advantage, since it is easily articulated among the different areas of knowledge, this fact allows an interdisciplinarywork freedom that is beneficial to the general educational process of the student. Thus the objective of this research is to analyzethe interference of the Curricular component of Physical Education as motivator of the scientific research in students who attendElementary School. As methodology was adopted the quantitative approach, with an applied nature, with exploratory objectives,through field research. The study was carried out with students of the 9th grade of Elementary School, a school located in themunicipality of Estância Velha, in Rio Grande do Sul. As a result, the difficulty of understanding scientific writing is recorded, andeven though, 52.9% of the students interviewed observed improvements in school performance, as well as, they came to betterunderstand the scientific work. In this way, the study concludes that the scope of the discipline of Physical Education contributesin the other disciplines and is related to the scientific doing, being associated in the development of creative abilities and, in thesystematization of ideas in an innovative way, in an effective interaction and articulation with the different areas of knowledge.